Using Electronic Active Student Responding for Students With EBD. (December 2020) - Riden, Benjamin S.; Taylor, Jonté C.; Mantzoros, Theoni
Teachers of students with emotional and behavioral disorders often struggle with increasing student participation while maintaining a positive classroom environment. Active student responding (ASR) occurs when a student says, writes, or engages in some observable response following a question. This article identifies and describes three electronic approaches to ASR and provides teachers with tips for effective implementation with students with emotional and behavioral disorders.